Elementary Technical Mathematics

Published by Brooks Cole
ISBN 10: 1285199197
ISBN 13: 978-1-28519-919-1

Chapter 10 - Section 10.5 - Finding Factors of Special Products - Exercise - Page 354: 40



Work Step by Step

This is a perfect square trinomial in the following manner $$ -bx^2 -12bx - 36b=-b(x^2+12x+36)=-b(x+6)(x+6) .$$ One can check as follows $$ -b(x+6)(x+6)=-b(x^2+12x+36)=-b(x^2+6x+6x+36)=-bx^2 -12bx - 36b .$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.